Pengaruh Perbedaan Jenis Substrat dan Kedalaman Terhadap Jumlah Juvenil Karang yang Menempel di Perairan Pulau Sambangan, Kepulauan Karimunjawa, Jepara - Hartono, Eko Puji; Munasik, Munasik; Wijayanti, Diah Permata (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Coral reef degradation caused by the human and natural factors. Human factors such as pollution and exploitation of marine resources is excessive. While natural factors such as waves, currents, brightness, substrate type and depth. This study aims to determine the effect of differences in substrate type and depth to the number of juvenile coral attached. Substrate used is a slab of concrete blocks and andesite which have been compiled into a series of collector substrate. Were of compile congcrete blok and andesit mounted at a depth of 3m and 10m. The study was conducted with experimental methods and data processed in the field by descriptive analysis. The observation station were using a purposive sampling method. The substrate was observed every month with 3 repetitions. After 6 mounth of observation the slabs of compile concrete blocks were tooh from the side and them. Taken were dipped in a chlorine solution of 10%. Juveniles determined attached identification and calculate. The number of juvenile corals on a andesite substrate at a depth of 3 meters by 14 induvidu the position of the water column and as many as 17 induvidu the bottom position, while at a depth of 10 meters as 11 induvidu at position 18 induvidu water column and bottom positions. While the number of juvenile corals are attached to the substrate concrete block at a depth of 3 meters by 24 induvidu the position of the water column and as many as 30 induvidu the bottom position, while at a depth of 10 meters by 17 induvidu at position 22 induvidu water column and bottom positions. The results may indicate that the differences in substrate type and depth of exercising influence over the settlement of juveniles.